Neural markers of methylphenidate response in children with attention deficit hyperactivity disorder and the impact on executive function - Wang, Anqi; Yang, Hua; Yang, Yue; Yang, Jie; Yang, Xiaowen; Wen, Qianhui; Wang, Qian; Liu, Hao; Luo, Rong (Frontiers in Psychiatry, 2025)
BackgroundAttention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder characterized by inattention, hyperactivity, and impulsivity. A core cognitive deficit in ADHD is executive function (EF) impairment, which significantly impacts daily life. Methylphenidate (MPH) is a widely used first-line treatment for ADHD, but objective biomarkers to assess treatment response are lacking. The aim of this study was to investigate the effects of MPH on executive function and identify potential neural biomarkers of response in children with ADHD using electroencephalogram (EEG).MethodsA total of 26 boys with ADHD (mean age 8.64 ± 1.30 years) participated in the study. All participants were treated with 18 mg/day of oral extended-release MPH in the morning for 8 weeks. Executive function was assessed using the BRIEF2 and Digit Span Test (DST), and event-related potentials (ERP) were measured at baseline and after 8 weeks of MPH treatment.ResultsAfter 8 weeks of MPH treatment, significant improvements were observed in several executive function domains. BRIEF2 scores, including inhibition, self-monitoring, shifting, emotional control, initiation, working memory, planning/organization, task monitoring, and material organization, were significantly reduced (P < 0.05). Behavioral performance in the Go/NoGo task also improved, with shorter correct response times and higher accuracy rates (P = 0.002, P = 0.009). EEG results revealed a reduction in Nogo-P300 latency at Fz, Cz and Pz compared to baseline (P<0.05).ConclusionsThe normalization of P300 latency following MPH treatment appears to be a reliable neural biomarker of positive treatment response in children with ADHD. MPH was associated with improvements in executive function, particularly in inhibitory control and working memory.